THE RISE OF LOCAL DALIT LEADERSHIP AND THE SPREAD OF AMBEDKARITE IDEOLOGY IN NAGPUR AND AMRAVATI DISTRICTS (1925–1956) - Meshram, Ranjit Kavindra; Tarare, Suraj Purushottam (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Dr. Babasaheb Ambedkar’s contribution to the social movements against social inequality in colonial India is exceptional. His social, educational, and political movements provided ideological and organizational foundations for the fight against untouchability. Ambedkar’s work was not limited to the national level but also had a wide impact at various regional levels. Particularly, in the Vidarbha region of Maharashtra, his ideas found significant expression. The districts of Nagpur and Amravati in Vidarbha became not just small centers of Ambedkarite thought but fertile grounds for building a broader movement. Nagpur was the site of many important events in Ambedkar’s life be it the historic announcement of his religious conversion or the revolutionary ceremony of Dhamm Diksha. Against this backdrop, Nagpur energized the social transformation struggle. Similarly, Amravati district saw the rise of Dalit leadership that was not merely imitative but created movements relevant to local conditions.In the 1920s, the untouchable community was deprived of education, rights, self-respect, and social dignity. As British colonial reforms slightly opened some doors, under Ambedkar’s leadership, the Dalit community began to awaken to new social consciousness. Local activists in Nagpur and Amravati not only limited this awareness to propaganda but transformed it into action that impacted social behavior. They organized local associations, held meetings, conducted awareness on religious conversion, and laid the groundwork for a broader social revolution. This research will conduct an in-depth analytical study of the rise of Dalit leadership in Nagpur and Amravati, their methods of work, their commitment to Ambedkar’s ideas, and how Ambedkarite ideology spread in these two districts. It will examine the work of local leaders, the establishment of organizations, the participation of women, initiatives related to Buddhist dhamma acceptance, and socio-political outcomes. The focus of this study will be on the expansion of the movement and the consequent ideological and social awakening of the Dalit community between 1925 and 1956.